ANALISIS BREAK EVEN POINT PADA USAHA KERIPIK SINGKONG “BAROKAH” DESA KARANG REJO KABUPATEN PESAWARAN - Suharto Suharto (Industrika : Jurnal Ilmiah Teknik Industri, 2017)
The purpose of an established business is to obtain profit or profit that can be used for survival. Likewise with the business of cassava chips "Barokah" in Karang Rejo Village Pesuat Pesawaran.Penelitian aims to find out how the value of Break Even Point aatu point home principal. This analysis is one of the tools used by the management company to be able to help in knowing how big a certain sales level, so the company does not get a profit and also not experience a loss (breakeven). The type of research used in this research is descriptive research with quantitative approach, the data source used is secondary data. Based on the results of the analysis can be seen that the BEP value of cassava chips business "Barokah" in the unit of 862 kg and if stated in ruiah of Rp. 10.185.454. Keywords: Break Even Point, Fixed Cost, Variable Cost